Variasi Campuran Limbah Sayur Kol dan Feses Sapi Untuk Meningkatkan Produktifitas Biogas: Studi Eksperimental - Ahmad Yani (Jurnal Teknologi Terpadu, 2022)
Biogas is a type of gaseous fuel obtained through the anaerobic fermentation process of organic matter into methane gas, one of the ingredients for making biogas is cow dung vegetable waste. The purpose of this study was to determine the variation of the mixture of vegetable col waste with cow feces on the efficiency and calorific value of biogas. The research method used is an experimental method on a scale of 20 liters of biogas digester volume. The results of the five variations of mixed vegetable col waste with cow feces showed that the highest biogas efficiency occurred in a mixture of 70% vegetable col waste with 30% cow feces with a value of 0.037%. While the lowest efficiency occurred in a mixture of 0% col vegetable waste with 100% cow feces with a value of 0.029%. The highest calorific value of biogas occurs in a mixture of 70% vegetable col waste with 30% cow feces with a value of 35,758.51 cal/ltr. While the lowest calorific value of biogas occurs in a mixture of 0% vegetable col waste with 100% cow feces with a value of 19,887.07 cal/ltr. Keywords: cow feces, vegetable waste col, efficiency, calorific value, biogas.